Taxonomic revision of the genus Amaranthus (Amaranthaceae) in Saudi Arabia - Hassan, Walaa A.; Al-Shaye, Najla A.; Alghamdi, Salma; Korany, Shereen M.; Iamonico, Duilio (Phytotaxa, 2022)
A taxonomic revision of the genus Amaranthus (Amaranthaceae) in Saudi Arabia, based on both field surveys and examination of harbarium specimens, is here presented. Collected exsiccata are kept the Herbaria PNUH and RO. An extensive literature was also analysed. Sixtheen non-hybrid taxa (twelve species) are recognized. Data about nomenclature (accepted names, main synonyms, and types), morphology, chromosome number, chorology (for native taxa) or alien status (for exotic taxa), occurrence in Saudi Arabia, ecology (preferential habitat, phenology, elevation), and taxonomic annotations are provided for each taxon. A diagnostic key is proposed. Four taxa (A. graecizans subsp. graecizans, A. graecizans subsp. sylvestris, A. graecizans subsp. thellungianus, and A. sparganicephalus) are native, whereas the other ones are to be considered aliens. A. dubius and A. blitoides var. blitoides are new for the national flora. Furthermore, the name A. sparganicephalus is neotypified on a specimen deposited at E and a nomenclatural change (A. blitum var. nanus comb. nov.) is proposed.